Pendampingan Penyusunan Laporan Keuangan Pesantren Berbasis Excel dan Laporan Pajak Tahunan Baitul Qur'An Berbasis Excel - Sinarti, Sinarti; Zelmiyanti, Riri; Utama, Doni Putra; Lestari, Nanik; Ikhlash, Muhammad; Riyadi, Sugeng; Zaenuddin, Muhammad (Jurnal Pengabdian kepada Masyarakat Politeknik Negeri Batam, 2023)
Abstract"”This service activity aims to continue the implementation of community service activities for the 2021 period, the output of which is PSAK 45 Socialization, preparation of accounting policies for Islamic Boarding Schools, and a simple Excel application for preparing financial reports. The location of the Islamic boarding school which will be used as a place for carrying out activities is in Tanjung Buntung, Bengkong District, Batam City, Riau Archipelago. The method of implementing the activities that will be used is the mentoring method and the Excel application development method. The output of this service is the application of excel-based financial reports, videos of community service activities, and tax reports. It is hoped that this community service activity will increase the knowledge, expertise and independence of partners' financial departments in preparing financial reports based on standards set by the Public Accountants Association professional organization and make maximum use of accounting policies and excel templates that have been made in previous community service activities and the preparation of tax reports . Another output is that the results of this community service activity will be published in journals or community service proceedings and reported in online media so that similar organizations can obtain information and establish mentoring cooperation with the Batam State Polytechnic. Keywords"”Islamic Boarding School Accounting, ISAK 35, Financial Statements, Accounting Policies